Ribosome slowdown triggers codon‐mediated mRNA decay independently of ribosome quality control. (18th January 2022) - Mishima, Yuichiro; Han, Peixun; Ishibashi, Kota; Kimura, Seisuke; Iwasaki, Shintaro
Abstract: The control of mRNA stability plays a central role in regulating gene expression patterns. Recent studies have revealed that codon composition in the open reading frame determines mRNA stability in multiple organisms. Based on genome‐wide correlation approaches, this previously unrecognized role for the genetic code is attributable to the kinetics of the codon‐decoding process by the ribosome. However, complementary experimental analyses are required to clarify the codon effects on mRNA stability and the related cotranslational mRNA decay pathways, for example, those triggered by aberrant ribosome stalling. In the current study, we performed a set of reporter‐based analyses to define codon‐mediated mRNA decay and ribosome stall‐dependent mRNA decay in zebrafish embryos. Our analysis showed that the effect of codons on mRNA stability stems from the decoding process, independent of the ribosome quality control factor Znf598 and stalling‐dependent mRNA decay. We propose that codon‐mediated mRNA decay is rather triggered by transiently slowed ribosomes engaging in a productive translation cycle in zebrafish embryos. Synopsis: Codons in mRNA not only determine amino acid sequences, but also affect mRNA stability in eukaryotes. Here, a novel high‐throughput reporter assay in zebrafish embryos uncovers that ribosome slowdown, but not aberrant stalling, causes codon‐mediated mRNA decay. Parallel analysis of codon effects (PACE) enables measurement of individual codon‐specific effects on mRNA stability in zebrafish embryos. Codon effects on mRNA stability correlate with tRNA levels and ribosome densities relative to A‐site codons. Modulation of tRNA availability alters the codon effects. Codon‐mediated mRNA decay is distinct from mRNA decay caused by aberrant ribosome stalling and ubiquitin ligase Znf598. Codon‐mediated mRNA decay occurs during productive translation cycles and involves ribosome slowdown. Abstract : Parallel analysis of codon effects (PACE) system differentiates codon‐mediated mRNA degradation from ribosome stall/Znf598‐dependent decay in zebrafish embryos.